PENGARUH TATA KELOLA GLOBAL AI TERHADAP KONTESTASI IDEOLOGI AS-TIONGKOK - Kinantika, Melati; Chantika Fitri, Anggiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rivalry between the United States and China is inseparable from ideological issues that are increasingly expanding into various fields. The technological advancements of the United States and China are now also competing in the field of artificial intelligence. Artificial intelligence is no longer merely a technological advancement but also a system that drives infrastructure development, economic progress, and resource utilization. AI serves as a new instrument to support the political direction of a country. Global AI governance has been established as a platform for cooperation and a guideline on how AI should be used in the global environment. However, the emergence of governance systems has complicated the relationship between these two countries because the ideological differences underlying the U.S. and China give rise to rivalry. As a result, both prioritize their own interests, leading to a struggle for hegemony by strengthening their respective national strategies.